(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تشكل فطريات البياض الدقيقي (Erysiphaceae) إحدى أهم المجموعات الفطرية, فهي تصيب العديد من النباتات البرية, الشجرية والعشبية وتصيب عدداً هاماً من المحاصيل الزراعية الحقلية والخضرية وكذلك الأشجار المثمرة ونباتات الزينة. قمنا وعبر جولات حقلية بإحضار العينات النباتية المصابة وفحصها وإجراء القياسات المختلفة عليها في المخبر, ومن ثم تحديد الأنواع التابعة للجنس Erysiphe خلال الفترة الزمنية 2000-2002. أظهرت الدراسة, حتى الآن, وجود /18/ نوعاً تنتمي إلى الجنس Erysiphe تتطفل على الكثير من العوائل النباتية تتبع /20/ فصيلة. وجدت أغلب الأنواع بطوريها الكونيدي والجنسي معاً (14 نوعاً), بينما وجد عدد قليل منها بطوره الكونيدي فقط (4 أنواع). تم تحديد أهم الصفات المورفولوجية المميزة لكل نوع منها, ودعم الوصف بقياسات مجهرية لأهم أجزاء الطورين الجنسي واللاجنسي. The powdery mildew fungi (Erysiphaceae) forms one of the most important fungi groups, infecting wild plants, weeds and many other fruit trees, filed crops, vegetables and ornamentals. We carried out a survey of the species of the genus Erysiphe in some sites of the Syrian coastal region during the period 2000-2002. The resultes showed an existence of (18) species of Erysiphe infecting various host plants in (20) different families. Most species (14) have been found in both the conidial and cleistothecium stages, whereas (4) species have been found only in conidial stage. The most important morphological characters of sexual and asexual stages have been determind. These were proved by microscopical measurements of the studied species.